2017
DOI: 10.17265/2159-5828/2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Development of Lactic Acid Bacteria in Bread Dough Enriched with Zinc and Selenium

Abstract: Abstract:The incorporation of lyophilized lactic acid bacteria in dough formulation is a current trend in bread making in order to achieve quality improvement and extension of shelf life of bread. Another major aspect for today's bread making industry is an increase of the biological value of bread, by addition of mineral substances that are deficient in bread (such as zinc and selenium). This is an effective approach to combat the existing mineral deficiency in population nutrition. The aim of the present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Zlateva et al. ( 2017 ) showed that applying a culture starter with Lactococcus lactis to sourdough wheat flour bread increased the biological value of the bread, extended shelf life, and improved sensory quality. Similar results were reported by Wu et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zlateva et al. ( 2017 ) showed that applying a culture starter with Lactococcus lactis to sourdough wheat flour bread increased the biological value of the bread, extended shelf life, and improved sensory quality. Similar results were reported by Wu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Lactococcus lactis in sourdough bread fermentation has been reported to improve the sensory attributes of the bread. Zlateva et al (2017) showed that applying a culture starter with Lactococcus lactis to sourdough wheat flour bread increased the biological value of the bread, extended shelf life, and improved sensory quality. Similar results were reported by Wu et al (2022), who also used Lactococcus lactis as a culture starter in sourdough wheat bread and demonstrated a positive effect on the concentrations of aldehydes, ketones, and furans and improved sensory attributes.…”
mentioning
confidence: 99%